Fiber Optic SPR Sensing Enhancement in NIR via Optimum Radiation Damping Catalyzed by 2D Materials - Sharma, Anuj K.; Kaur, Baljinder (IEEE photonics technology letters, 2018)
Fiber optic surface plasmon resonance (FOSPR) sensor with samarium-doped chalcogenide core, polymer clad, Ag layer, and 2D material (graphene and MoS 2 ) monolayer is studied in near-infrared seeking sensitive and accurate determination of malignancies in human liver tissues. The analysis shows that the presence of 2D material significantly catalyzes the optimum radiation damping (ORD) in the FOSPR structure, causing massive increase in its figure of merit (FOM). At ORD, i.e., 803.9-nm wavelength ( λ ) and 35.7-nm Ag layer thickness ( d_{m} ), the FOM of graphene-based FOSPR sensor races to 6904.012 RIU −1 . Similarly, at λ = 1099.35 nm and d_{m} = 29.8 nm, MoS 2 -based FOSPR sensor's FOM shoots to 5897.082 RIU −1 . The comparison reveals that the above FOM values are way better than for the existing FOSPR sensors. For biosensing, MoS 2 -based FOSPR sensor should be used, as its longer ORD wavelength (1099.35 nm) leads to reduced Rayleigh scattering and lesser photodamage of tissue. For other sensing applications, graphene-based FOSPR sensor at its ORD condition can be used.